Experience of an on-line course about ABA in new psychotherapies - Valero-Aguayo, Luis (My University, 2014)
In Spain they are few courses about Applied Behavior Analysis in clinical settings, generally are classroom or seminaries into some postgraduate courses. They are no experiences with on-line courses about Behaviour Analysis in general in a university context. We present the experience and results of a course completely on-line through Moodle software in the University of Malaga (Spain) during three years. The course was about ABA in new psychotherapies of third generation (ACT, FAP, and Activation). It was over 20 hours (2 European University Credits). The topics treated were: experimental basis and fundamental of new psychotherapies, characteristics and application of ACT, management of FAP, application of BA in depression; and the efficacy of psychotherapies. The course was learning programmed with different texts, videos, questions, exercises and homework activities. Also the development of learning processes was cumulative, so the student did not read a lesson if he/she had not completed the lesson before. The participants were a total of 64 students (62% from University of Malaga, and 48% from other cities or professionals in clinical settings). The amount of students and their origins were similar during three years. The results showed a good improvement of students, with 8.9, 8.6 and 9.1 as an academic chart (A in all cases), and good satisfaction from professors and students in the final valuation questionnaire.
Keywords: Psicoterapia - Estudio y enseñanza; Enseñanza asistida por ordenador; Curso on-line; Nuevas psicoterapias; New psychotherapies; On-line course